ANALISIS LEVEL KOGNITIF SOAL PAS 1 IPA PADA UPT SP SDN KARANGTENGAH 3 KOTA BLITAR - Lilik Handayani; Titik Harsiati; Aynin Mashfufah (LPPM Institut Pendidikan Nusantara Global, 2022)
As a form of summative assessment, Final Semester Assessment (PAS) 1 needs to be carried out. This is not only to measure students' abilities but more on the follow-up that needs to be done after completing the PAS implementation. The purpose of this study was to determine the cognitive level of the IPA PAS questions. The method used in this research is descriptive qualitative. With research on the cognitive level, it is hoped that in the future it will be able to improve HOTS questions and students can improve their numeracy literacy skills. After analyzing the PAS 1 questions, it was found that out of 50 questions there were 37 questions with a percentage of 74% at the LOTS level in the C1-C3 range. and there are 13 questions or 26% with the HOTS level or in the C4-C6 range. Based on these data, it can be concluded that the Class 6 Science PAS questions at UPT SP SDN Karangtengah 3 are still at the LOTS level. In the future, research is needed that does not only analyze the cognitive level but can also relate it to literacy, so that students will find it easier to work on HOTS questions.